2008
DOI: 10.1111/j.1365-2125.2008.03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there evidence for biased reporting of published adverse effects data in pharmaceutical industry‐funded studies?

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Industry‐funded studies tend to emphasize favourable beneficial effects of the sponsor's product, but we do not know if reports of adverse effects are downplayed. • Pharmaceutical companies are required to collate and accurately report adverse effects data in order to fulfil regulatory requirements. WHAT THIS STUDY ADDS • The bias found in the studies looking at the association between industry funding and reporting of beneficial effects may not be as prominent whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 22 publications
0
25
0
4
Order By: Relevance
“…Published reports of clinical trials in medical journals are another important source of drug information for physicians. Unfortunately, a growing body of literature has documented disturbing problems with the quality of published research reports, particularly when they are industry sponsored, including selective publication of trials with favorable results (25-29), selective reporting of favorable outcomes (26,30,31), and "spinning" results and conclusions to overstate the benefit of an intervention (32)(33)(34) or to minimize the side effects (35).…”
Section: Side Effects (Excerpt)mentioning
confidence: 99%
“…Published reports of clinical trials in medical journals are another important source of drug information for physicians. Unfortunately, a growing body of literature has documented disturbing problems with the quality of published research reports, particularly when they are industry sponsored, including selective publication of trials with favorable results (25-29), selective reporting of favorable outcomes (26,30,31), and "spinning" results and conclusions to overstate the benefit of an intervention (32)(33)(34) or to minimize the side effects (35).…”
Section: Side Effects (Excerpt)mentioning
confidence: 99%
“…COIs have the potential to affect how information is presented in scientific journals and medical education forums. 7,8 As a result, many medical professional organizations, including the American Society of Clinical Oncology (ASCO), have COI policies in place to address the industry relationships held by…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, previous research of systematic reviews of adverse effects from 1994 to 2011 has indicated that, few attempts are made to search for unpublished data or industry funded data (10,15). This may be due to an expected low return or the difficulties of searching for unpublished data or in obtaining and incorporating unpublished data into systematic reviews (16) or a concern that unpublished data is not peer reviewed.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%